An analysis of the relationship between stock prices and financial ratios of banks based on the ASEAN-4 - Ko, Rica Anne A. (Animo Repository, 2023)
This study examines the relationship between financial performance and stock prices of banks in the ASEAN-4 countries (the Philippines, Thailand, Vietnam, and Malaysia). Utilizing multiple regression analysis, the research analyzes the relationships between earnings per share, dividend per share, core capital, liquidity ratio, and the stock prices of selected banking institutions. Data is collected from secondary sources, including financial reports from 2013 to 2022. Descriptive statistics summarize the data, revealing significant positive correlations between financial performance indicators and stock prices of the selected banks. Earnings per share, dividend per share, core capital, and liquidity ratio are identified as crucial factors influencing stock prices, indicating their importance in investment decisions. The findings contrast with previous research in Kenya, where only dividend per share showed a significant relationship with stock prices. This emphasizes the importance of understanding regional dynamics in evaluating stock performance. The study recommends regulators to educate the public about the significance of banking ratios in determining share prices, while banks should reevaluate their dividend policy. Academics and future researchers are encouraged to further explore this topic, and investors can benefit from the insights to make well-informed investment decisions. Overall, this research sheds light on the interplay between financial performance and stock prices in the ASEAN-4 banking sector, providing valuable information for stakeholders to enhance financial stability and navigate the competitive banking landscape of the region.